2001
DOI: 10.1080/mmy.39.3.277.282
|View full text |Cite
|
Sign up to set email alerts
|

Canine paracoccidioidomycosis: a seroepidemiologic study

Abstract: Sera from 305 dogs were analyzed by enzyme-linked immunosorbent assay (ELISA) to determine presence of the antibody anti-gp43, which reacts to a specific antigen of Paracoccidioides brasiliensis. The dogs were divided into three groups according to their origin: urban dogs (animals with little or no contact with rural areas); suburban dogs (from the urban outskirts); and rural dogs. There was a significant difference between groups (P < 0.05). Rural dogs reacted positively in 89.5% of cases, followed by suburb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 14 publications
4
19
0
4
Order By: Relevance
“…The high frequency of infection by P. brasiliensis observed in dogs living in paracoccidioidomycosis endemic areas, the low incidence of natural disease reported in this species and experimental data with adult animals suggest that adult dogs are resistant to the development of paracoccidioidomycosis (18,24). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The high frequency of infection by P. brasiliensis observed in dogs living in paracoccidioidomycosis endemic areas, the low incidence of natural disease reported in this species and experimental data with adult animals suggest that adult dogs are resistant to the development of paracoccidioidomycosis (18,24). …”
Section: Resultsmentioning
confidence: 99%
“…Epidemiological studies have demonstrated that infection by P. brasiliensis occurs in domestic and in wild animals (6,7,8,11,15,18,22,24,25). A high frequency of infection was observed in dogs from areas endemic for paracoccidioidomycosis in Brazil (18,24), although to date, only two cases of natural disease have been reported (4,12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rabbits experimentally infected with P. brasiliensis produced antibodies against gp43, suggesting that this antigen can be useful for epidemiological studies of PCM in this species. Other domestic animals such as dogs, cows, sheep, chickens and goats also showed humoral immune response against gp43 antigen after immunisation with P. brasiliensis cells.…”
Section: Discussionmentioning
confidence: 99%
“…The infection of domestic and wild animals by P. brasiliensis occurs frequently as reported in several epidemiological studies with dogs, horses, cattle, sheep, chickens, goats coati‐mundi, felines, monkeys and armadillos, although natural disease was reported only in two dogs, a cat and a southern two‐toed sloth …”
Section: Introductionmentioning
confidence: 98%